2014
DOI: 10.1016/j.ajpath.2014.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Activated Parietal Epithelial Cells on the Glomerular Tuft Distinguishes Early Focal Segmental Glomerulosclerosis from Minimal Change Disease

Abstract: In rodents, parietal epithelial cells (PECs) migrating onto the glomerular tuft participate in the formation of focal segmental glomerulosclerosis (FSGS) lesions. We investigated whether immunohistologic detection of PEC markers in the initial biopsies of human patients with first manifestation of idiopathic nephrotic syndrome with no immune complexes can improve the sensitivity to detect sclerotic lesions compared with standard methods. Ninety-five renal biopsies were stained for claudin-1 (PEC marker), CD44 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 26 publications
(32 reference statements)
14
64
0
Order By: Relevance
“…19,23,55 The fifth major and novel finding of our study was that the de novo expression of CD74 in PECs during glomerulonephritides might serve as a novel sensitive marker of PEC injury and activation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…19,23,55 The fifth major and novel finding of our study was that the de novo expression of CD74 in PECs during glomerulonephritides might serve as a novel sensitive marker of PEC injury and activation.…”
Section: Discussionmentioning
confidence: 95%
“…The upregulation of CD44 in resident glomerular cells and the de novo expression in PECs during glomerular diseases was previously documented by us and others. 19,29,30 We extend these data herein by quantitative analyses of CD44 mRNA expression in microdissected glomeruli showing a significant, up to eightfold, upregulation of CD44 in RPGN and IgAN (Supplemental Figure 1B).…”
Section: Mif and Cd74 Expression In Human Kidney Tissuementioning
confidence: 90%
See 1 more Smart Citation
“…A novel paradigm showed that the inconspicuous cells lining Bowman's capsule, the parietal epithelial cells, are crucially involved in the pathogenesis of not only crescentic glomerulonephritis but also most types of glomerulosclerosis (119)(120)(121)(122)(123)(124) (Figure 2). The identification of specific molecules resulting in activation of these cells might lead to novel therapeutic options in glomerulosclerosis.…”
Section: The Role Of Glomerular Cellsmentioning
confidence: 99%
“…Disruption of this interaction owing to HO-1 deficiency in nuclei of podocytes would, therefore, be expected to increase oxidative stress level and this could account for the increased lamins A and C expression observed [33] . Finally, the increase in annexin A3 expression (2.04-fold) in Hmox1 -/-glomeruli is of potential interest, as this protein was recently identified as a novel parietal glomerular epithelial cell marker indicative of a sclerosing process [34] .…”
Section: Discussionmentioning
confidence: 99%